Circular RNA circCCNT2 is upregulated in the anterior cingulate cortex of individuals with bipolar disorder - Lin, Rixing; Lopez, Juan Pablo; Cruceanu, Cristiana; Pierotti, Caroline; Fiori, Laura M.; Squassina, Alessio; Chillotti, Caterina; Dieterich, Christoph; Mellios, Nikolaos; Turecki, Gustavo (Translational Psychiatry, 2021)
Gene expression dysregulation in the brain has been associated with bipolar disorder, but little is known about the role of non-coding RNAs. Circular RNAs are a novel class of long noncoding RNAs that have recently been shown to be important in brain development and function. However, their potential role in psychiatric disorders, including bipolar disorder, has not been well investigated. In this study, we profiled circular RNAs in the brain tissue of individuals with bipolar disorder. Total RNA sequencing was initially performed in samples from the anterior cingulate cortex of a cohort comprised of individuals with bipolar disorder (N = 13) and neurotypical controls (N = 13) and circular RNAs were identified and analyzed using “circtools”. Significant circular RNAs were validated by RT-qPCR and replicated in the anterior cingulate cortex in an independent cohort (24 bipolar disorder cases and 27 controls). In addition, we conducted in vitro studies using B-lymphoblastoid cells collected from bipolar cases (N = 19) and healthy controls (N = 12) to investigate how circular RNAs respond following lithium treatment. In the discovery RNA sequencing analysis, 26 circular RNAs were significantly differentially expressed between bipolar disorder cases and controls (FDR < 0.1). Of these, circCCNT2 was RT-qPCR validated showing significant upregulation in bipolar disorder (p = 0.03). This upregulation in bipolar disorder was replicated in an independent post-mortem human anterior cingulate cortex cohort and in B-lymphoblastoid cell culture. Furthermore, circCCNT2 expression was reduced in response to lithium treatment in vitro. Together, our study is the first to associate circCCNT2 to bipolar disorder and lithium treatment.